Cerium oxide nanoparticles: the regenerative redox machine in bioenergetic imbalance. (February 2017) - Pezzini, Ilaria; Marino, Attilio; Turco, Serena Del; Nesti, Claudia; Doccini, Stefano; Cappello, Valentina; Gemmi, Mauro; Parlanti, Paola; Santorelli, Filippo M.; Mattoli, Virgilio; Ciofani, Gianni
Aim: Owing to their catalytic properties as reactive oxygen species scavengers, cerium oxide nanoparticles (nanoceria) have become an extremely promising candidate for medical applications, especially in the treatment of diseases where oxidative stress has been proposed as one of the main pathogenesis factors.Materials & methods: In this work, nanoceria antioxidant power has been tested in primary cultured skin fibroblasts, derived from healthy individuals, by evaluating the mitochondrial function both in basal condition and after an oxidative insult.Results & conclusion: Combined with a clear lack of toxicity, antioxidant activity makes nanoceria promising in a wide range of clinical applications sharing the common signature of a global bioenergetic dysfunction.